2014
DOI: 10.1016/j.adengl.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Circumscribed Palmar or Plantar Hypokeratosis 10 Years After the First Description: What Is Known and the Issues Under Discussion

Abstract: This review of the literature on palmoplantar hypokeratosis, a process that was first indentified only 10 years ago, discusses the current state of our understanding, the therapeutic options available, and the debate about etiology. Forty-four publications reporting 69 cases were found. Palmar or plantar hypokeratosis occurs mainly in women (76.8%) and age at the time of a first visit to a physician ranges from 42 to 84 years. Most cases present between the ages of 51 and 70 years. The majority of patients hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Since the first description of CPH in 2002, further cases have been reported with similar clinical and histological features. According to a recent review, most reported lesions were single, mainly located on the right palm, particularly the thenar region, and had been present for a long period, with a mean duration of 12.8 years. Only 10 (13.0%) of the 69 identified cases had multiple (two or three) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of CPH in 2002, further cases have been reported with similar clinical and histological features. According to a recent review, most reported lesions were single, mainly located on the right palm, particularly the thenar region, and had been present for a long period, with a mean duration of 12.8 years. Only 10 (13.0%) of the 69 identified cases had multiple (two or three) lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions had an erythematous surface with clear-cut edges. 2 Up to now, 86 cases have been published in the literature (Table 3). No one had history of trauma (Fig.…”
Section: Case Reportsmentioning
confidence: 99%
“…2,4,11,20,29,41 The most common locations are: palms (thenar and hypothenar regions) and soles. 2,4,11,20,29,41 The most common locations are: palms (thenar and hypothenar regions) and soles.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Nevertheless, due to the frequent lack of efficacy of these treatments and the benignancy of this entity, the observational attitude is an adequate option. 9 erythematous lesion on the metatarsal region of his right sole (Fig. 1A).…”
Section: Case Reportmentioning
confidence: 99%